"Nomadin-Sein" im "Dorf der Solidarität" - Eine kritische Ethnografie zu Camps für Rom_nja in Rom - Pagano, Simona (Universitätsverlag Göttingen, 2019)
In Italy, Solidarity Villages are state-provided places of accommodation for Romani people. In Rome, they are typically fenced off areas equipped with low-quality portable housing. In the media, these halting sites are often represented as a culturally appropriate housing solution. Yet, these camps are neither temporary halting places nor cultural forms of housing. Rather, they are places of segregation, conflict and negotiation-sites where racism, sexism and a particular way of dealing with poverty and migration condense. Beginning with the declaration of a Nomad Emergency in 2008, Simona Pagano documents the emergence of the spatial logic of the camp and offers an intersectional analysis of the complex power relations that shape the lives of its female residents. Drawing on ethnographic engagement, as well as interviews with institutional actors and civil society organizations, Pagano shows that the camps are often places of segregation and control, of profit generation and violence, but also, spaces of solidarity, homemaking and friendship.